Development of Low Cost Miniature USB Based Data Acquisition System for Biomedical Instrumentation (Bangladesh Journal of Medical Physics, 2018)
In biomedical instrumentation, computer based data acquisition system is required for recording of physiological parameters and bioelectric signals, which allows signal processing, display, analysis and storage in digital media. However, Most of the commercially available PC based Data Acquisition systems are of very high cost and requires specific commercial software, again at a very high cost. Moreover, if the data is not stored in raw binary or known format, it is not possible for the user to use the data in other system or software of their own choice. Therefore, a low cost, simple and open source PC based data acquisition system for biomedical application would be very useful for biomedical instrument developers and researchers in the low resource countries. In this work, we present such development of data acquisition system. The developed system utilizes an 8-bit ordinary low cost microcontroller and some electronic circuit component to develop the data acquisition system and implementation of USB 1.1 (Universal Serial Bus) interface to PC. The onboard 10-bit ADC of the microcontroller was used for analog data sampling. Two sampling and data transfer mode is implemented, (i) Continuous mode with low sampling rate (800 sample/sec) and practically real time plotting and (ii) Batch mode, with high sampling rate (76.9 k sample/sec) but with batch type plotting. To evaluate the system, PC side GUI (Graphical User Interface) software was also developed. The GUI of system shows that a test sinusoidal signal is reproduced very nicely without any amplitude and phase distortion within the frequency band of 1 to 10 KHz. The system is suitable for low frequency bioelectric signals like ECG, EEG etc. and as well as high frequency signal like EMG, NCV etc. The system is low cost, miniature, simple, and efficient and being used in several indigenously developed medical devices like ECG, EMG, NCV and FIM [Rabbani et al, 1999] at the authors’ department with excellent satisfactory results.Bangladesh Journal of Medical Physics Vol.10 No.1 2017 1-11